The Relationship Between Friendship Quality and Subjective Well-Being Among Students Of X Senior High School, South Tambun - Trisnawati, Novita Ananda; Abdillah, Rijal; Supriyadi, Tugimin; Dayita, Hema (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the relationship between friendship quality and subjective well-being among students of SMA X Tambun Selatan. Adolescence is a developmental stage characterized by a strong need for peer support, making friendship quality an important factor that may influence adolescents’ psychological well-being. This research employed a quantitative approach using a correlational method. The participants consisted of 130 tenth- and eleventh-grade students selected through purposive sampling. The instruments used in this study included a friendship quality scale based on Parker Asher’s (1993) theory and a subjective well-being scale adapted from Diener’s (1984) concept. Descriptive analysis indicated that most students had friendship quality within the moderate to high categories. Meanwhile, their subjective well-being levels fell within the moderate category. Pearson correlation analysis showed a strong and significant positive relationship between friendship quality and subjective well-being (r = 0.718, p 0.001). These findings suggest that the higher the friendship quality students experience, the higher their level of subjective well-being. Overall, this study highlights that positive and supportive friendships play an important role in enhancing adolescents’ psychological well-being. The results of this research may serve as a basis for schools, parents, and counselors to foster environments that support the development of healthy social relationships among students.